2022
DOI: 10.1002/ehf2.13824
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate recognition of own comorbidities is associated with poor prognosis in elderly patients with heart failure

Abstract: Aims A patient's understanding of his or her own comorbidities is part of the recommended patient education for those with heart failure. The accuracy of patients' understanding of their comorbidities and its prognostic impact have not been reported. Methods and resultsPatients hospitalized for heart failure (n = 1234) aged ≥65 years (mean age: 80.1 ± 7.7 years; 531 females) completed a questionnaire regarding their diagnoses of diabetes, malignancy, stroke, hypertension, chronic obstructive pulmonary disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…The FRAGILE‐HF study is a multicenter prospective observational study conducted in Japan to investigate the association between multidomain frailty and prognosis in older patients with HF. 12 , 31 , 32 , 33 A total of 1332 patients admitted to 15 hospitals in Japan were enrolled between September 2016 and March 2018. The study inclusion criteria were as follows: patients aged ≥65 years, diagnosed with HF, and capable of walking at the time of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The FRAGILE‐HF study is a multicenter prospective observational study conducted in Japan to investigate the association between multidomain frailty and prognosis in older patients with HF. 12 , 31 , 32 , 33 A total of 1332 patients admitted to 15 hospitals in Japan were enrolled between September 2016 and March 2018. The study inclusion criteria were as follows: patients aged ≥65 years, diagnosed with HF, and capable of walking at the time of discharge.…”
Section: Methodsmentioning
confidence: 99%
“…This was a post hoc analysis of the FRAGILE‐HF study, a prospective multicenter registry aimed at evaluating the prevalence, overlap, and prognostic value of physical frailty, social frailty, and cognitive dysfunction in older patients with heart failure. The detailed protocol of the FRAGILE‐HF study has been previously reported 15–17 . In total, 1332 patients hospitalized for heart failure, aged ≥65 years, and able to ambulate at discharge were registered between September 2016 and March 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed protocol of the FRAGILE-HF study has been previously reported. [15][16][17] In total, 1332 patients hospitalized for heart failure, aged ≥65 years, and able to ambulate at discharge were registered between September 2016 and March 2018. Heart failure was defined on the basis of the Framingham criteria.…”
Section: Study Populationmentioning
confidence: 99%
“…In total, the study enrolled 1,332 hospitalized patients with HF aged 65 years or older, who were capable of ambulation upon discharge, from 15 hospitals across Japan. 49) 50) 51) Using the data, we created an overlap diagram, as shown in Figure 1 . Our group previously highlighted the significance of multidomain frailty (i.e., physical, cognitive, and social domains) assessed by both the cumulative deficit and phenotypic models 49) 52) ; however, physical frailty defined by the Fried phenotype model is regarded as frailty in this analysis to enable the easy understanding of the interaction of these four entities.…”
Section: Overlap In Frailty Sarcopenia Cachexia and Malnutrition In P...mentioning
confidence: 99%